Giving Youth Athletes a Voice in Award Selection and Program-Goal Evaluation. (1st November 2016) - Mitchell, Murray
Abstract : Young athletes are bombarded with images and messages in the media about what sport is supposed to represent. In addition to coping with the potentially negative influences of the media, coaches also face having to address the variable influences of their athletes' peers and parents. This article presents a rationale and a relatively simple method for soliciting youth athlete input in the selection of key awards which can simultaneously yield insight into athlete perceptions and future program goals. The method presented here can also be used to gain insight into a variety of other sport program aspects, such as athletes' understanding of individual skill and team strategy needs, perceptions of desirable moral and ethical behavior, and the influence of comments from peers, parents and coaches. The important message is that "athletes' voices matter" and that young athletes' input can provide insight into the influence of sport on their lives now and in the future.